1999
DOI: 10.1007/bf03038890
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for tumors of the skull base

Abstract: Charged particle beams are ideal for treating skull base and cervical spine tumors: dose can be focused in the target, while achieving significant sparing of the brain, brain stem, cervical cord, and optic nerves and chiasm. For skull base tumors, 10-year local control rates with combined proton-photon therapy are highest for chondrosarcomas, intermediate for male chordomas, and lowest for female chordomas (94%, 65%, and 42%, respectively). For cervical spine tumors, 10-year local control rates are not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
231
1
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(260 citation statements)
references
References 42 publications
17
231
1
9
Order By: Relevance
“…Although some authors have reported an increase in tumor-free intervals after using radiotherapy for local control [26,32], others have reported radiotherapy has little influence on overall survival [8,9,28]. Two studies advocated the use of hadrons (ie, highdose protons or charged particles, such as carbon ions or helium) to improve the radiobiologic effect, mainly in cases of base of skull disease [17,23]. The physical and ballistic properties of hadrons allow delivery of higher doses to the target volume, while sparing organs at risk [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have reported an increase in tumor-free intervals after using radiotherapy for local control [26,32], others have reported radiotherapy has little influence on overall survival [8,9,28]. Two studies advocated the use of hadrons (ie, highdose protons or charged particles, such as carbon ions or helium) to improve the radiobiologic effect, mainly in cases of base of skull disease [17,23]. The physical and ballistic properties of hadrons allow delivery of higher doses to the target volume, while sparing organs at risk [7].…”
Section: Discussionmentioning
confidence: 99%
“…Prescribed tumour doses ranged from 63.4 to 79.4 CGE and the median dose to the optic structures in injured patients was 62.1 CGE. 10 Both of our patients with visual loss were female receiving tumour doses of 75 and 83.5 CGE. These proton therapy doses are in accordance with the Proton Radiation Oncology Group Trial (PROG 85-26 Study).…”
Section: Discussionmentioning
confidence: 72%
“…44 The introduction of high dose, high precision protontherapy in the mid-seventies at Massachusetts General Hospital, Boston, turned out to be a breakthrough, with approximately two-third of patients remaining alive with NED at 3-4 years in SB, and cervical-S locations. 45 This favorable outcome has been reproduced by multiple teams in US, Europe and Japan. [46][47][48] Doses were progressively upgraded to 75 Gy (EBR) (Gy (EBR) = physical dose × an estimated mean 1.1 RBE) and more, conventionally fractionated, at the price of an acceptable toxicity.…”
Section: Review Of Literaturementioning
confidence: 90%
“…[45][46][47][48]51,53 Pediatric CHs seem to fare better compared with their adult counterparts: 60-100% and 80-100%, respectively. 13,30,50,54,55 Nonetheless, younger children were frequently excluded in earlier series dealing with protons (since they require special attention, such as general anesthesia).…”
Section: Review Of Literaturementioning
confidence: 98%